Juridical Analysis of Cybercrime Carding: Crime of Credit Card and ATM Data Manipulation in Legal Perspective - Sarles Gultom; Van Lodewijk Purba; Anggun Pasaribu (KOLABORASI: Journal of Multidisciplinary, 2025)
Cybercrime carding, which involves the manipulation of credit card or ATM data, has frequently occurred in Indonesia and has gained significant international attention due to the risks associated with the misuse of technology in the digital information era. Several key issues require examination, including the factors causing cybercrime data manipulation, the modus operandi of cybercrime carding offenses, and the challenges and efforts in addressing this crime. The study, conducted using a library research method, concludes that cybercrime carding is driven by various factors such as rapid technological advancement, individuals testing their internet technology skills, socio-economic conditions, technical vulnerabilities, weak banking supervision systems, user negligence, inadequate network security, and lack of control by society and law enforcement agencies. The modus operandi of cybercrime carding includes Unauthorized Access to Computer Systems and Services, Illegal Content, Data Forgery, Cyber Espionage, Cyber Sabotage and Extortion, Offenses against Intellectual Property, and Infringements of Privacy. However, legal enforcement faces significant obstacles, including inadequate legal frameworks, limited investigative capabilities, insufficient evidence, and a lack of forensic computing facilities. One of the current efforts to combat cybercrime, including carding, is the formulation of the Draft Law on Electronic Information and Transactions (RUU ITE), which aims to establish comprehensive legal provisions for addressing cybercrime offenses in Indonesia.